Jamun Seed: A Review on Bioactive Constituents, Nutritional Value and Health Benefits - Yamini Tak; Manpreet Kaur; Mool C. Jain; Mahesh Kumar Samota; Nirmal Kumar Meena; Gurpreet Kaur; Rajendra Kumar; Daisy Sharma; José M. Lorenzo; Ryszard Amarowicz (Polish Journal of Food and Nutrition Sciences)
Jamun fruit, a member of the Myrtaceae family, is commercially grown in tropical and subtropical areas of the world for its fruits with sweet, sour, and astringent luscious flesh. Seeds of jamun fruits are discarded as trash during the industrial processing of fruit pulp into beverages, jellies, jam, vinegar, wine, and squash. These seeds are a potential source of bioactive compounds including hydrolysable tannins, phenolic acids, flavonoids, other phenolics, terpenoids, phloroglucinol derivatives and saponins, which have been endorsed several biological activities, such as antidiabetic, anticancer, anti-inflammatory, antioxidant, antimicrobial, antihyperlipidemic and antihypercholesterolemic, as well as cardioprotective, hepatoprotective and neuroprotective properties. High contents of carbohydrates, dietary fiber, minerals, and ascorbic acid have also been found in jamun seeds. However, potential utilization of these seeds as innovative implements for health benefits has not yet been fully understood. We aim to compile scientific research and recent advances on jamun seed nutritional profile, bioactive compounds composition, bioactive properties, and their potential as an ingredient in functional food formulation.